2023
DOI: 10.1002/chem.202203528
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Stabilization of a Lithium Ion with a Silylene

Abstract: Herein, we report the stabilization of lithium‐ion as the source of lithium to use as a trans‐metalation reagent [{PhC(NtBu)2Si(tBu)Li}2I(tBuN)2CPh] (1). The reaction of 3 equivalents of the LSitBu (L=PhC(NtBu)2) and lithium iodide at low temperature leads to a silylene stabilized lithium‐ion with an additional coordination of amidinate ligand. Compound 1 shows two four membered and one six membered ring as confirmed by QTAIM calculations. Whereas the reaction of the LSiCl with 1.5 equivalents of carbodiimide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Slow evaporation of the solvent yielded red crystals, and the single-crystal X-ray diffraction (XRD) experiment confirmed the structure of silaimine 2 , reminiscent of the postulated IntB (Figure ). Unlike in the literature-known examples, ,, in this case, the isonitrile functions as a donor to the silicon atom and cannot be removed from the compound without decomposition. Although the silicon atom is clearly tetracoordinated, its coordination by the carbazolyl ligand, the bromine atom, and the N1 atom is close to trigonal planar with a sum of the bond angles of 349°.…”
Section: Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Slow evaporation of the solvent yielded red crystals, and the single-crystal X-ray diffraction (XRD) experiment confirmed the structure of silaimine 2 , reminiscent of the postulated IntB (Figure ). Unlike in the literature-known examples, ,, in this case, the isonitrile functions as a donor to the silicon atom and cannot be removed from the compound without decomposition. Although the silicon atom is clearly tetracoordinated, its coordination by the carbazolyl ligand, the bromine atom, and the N1 atom is close to trigonal planar with a sum of the bond angles of 349°.…”
Section: Results and Discussionmentioning
confidence: 91%
“…19,21−25 The reaction of silylenes with carbodiimides is an alternative way to access silaimines, thereby avoiding the use of hazardous organoazides. Roesky showed that both amidinato chlorosily- 27 Thus, as the experimental results indicate, a balanced steric bulk of the combined silylenes and azides is required for the stabilization of the Si�N bond.…”
Section: ■ Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This property causes the Sb–Si π-bonding to be polarized, which can readily lead to dimerization or polymerization . A great variety of alkene analogues featuring a heteronuclear double bond between the identically heavier Group 14–15 elements was synthesized following the original discovery of the first stable silaimine >SiN and silaphosphene >SiP derivatives. The search for the formation of multiply bonded silicon compounds with Group 15 elements remains unbroken throughout the last decades and even is intensified for this most fascinating topic in silicon chemistry . Last year, major results could be added to the isolation of silylene moieties bound to Group 15 elements .…”
Section: Introductionmentioning
confidence: 99%
“…Such lack of isolable stiba‐ and bismasilenes provoked us to challenge the preparation of a doubly bonded heavy analogues R 2 Si=Ear (E=P, Sb, Bi), of the Schiff base derivatives. Surprisingly the reactivity of amidinate stabilized silylene towards antimony‐based compound remained almost unexplored [10b–h] . Which embarked us to synthesize phosphasilenes >Si=P− and its heavy homologue stibasilene >Si=Sb− using advantage of the above‐described unified synthetic approach, unfortunately could not obtained the bismasilenes.…”
Section: Introductionmentioning
confidence: 99%